Assessing The Lean Behavior in Hospital Lean Implementation: A Case Study - Kabib Abdullah (Syntax Idea)
The application of lean in several hospitals in Indonesia, one of which is required by the change in the BPJS financing system from Fee for Service towards Indonesia Case Based Groups (INA CBGs) where health service providers must provide services according to their needs without any reduction in quality. The application of lean behavior in hospital lean management in order to reduce resistance to all forms of change that must be made to meet all challenges in the era of universal coverage of health financing where hospitals must act effectively and efficiently in order to continue to survive and succeed in providing health services to the community. This research is a cross-sectional quantitative study. The research instrument is in the form of a questionnaire through the google form link. Analysis using SEM (structural equation model) with Smart PLS. The results showed that Self Eficacy significantly has a direct effect on Readiness (Betha=0.512, t = 9.262, p-value 0.00), Personal Valency significantly has a direct effect on Readiness (Betha=0.333, t = 5.344, p-value 0.00), Readiness significantly affects Lean Behavior (Betha=0.373, t = 6.577, p-value 0.00), Intentions significantly directly affect Lean Behavior (Betha=0.459, t = 8.454, p-value 0.00), Readiness significantly affects Intentions (Betha=0.653, t = 14.577, p-value 0.00). Intentions (Z2) are significant mediators of readiness (Z1) relationships to Lean Behavior(Y) (partial types of mediation) , Readiness(Z1) are significant mediators of Self Eficacy (X1) relationships to Lean Behavior(Y) through Readiness(Z1) (Partial types of mediation) , Readiness(Z1) are significant mediators of Personal valency (X2) relationships to Lean Behavior(Y) through Readiness(Z1) (Partial types of mediation), Readiness(Z1) and intention(Z2) are significant mediators of Self Eficacy relationships (X1) to Lean Behavior(Y)(Partial type mediation), Readiness(Z1) and intention(Z2) significantly mediator of Personal valency (X2) relationship to Lean Behavior(Y)(Partial type mediation) , Readiness(Z1) significant to mediator of Self Eficacy (X1) relationship to Intentions (Z2)(Partial type mediation), Readiness(Z1) significant mediator of Valency Persoal relationship (X2) to Intentions (Z2)(Partial type mediation). The effect of readiness on intentions has the highest value, readiness has a significant influence on lean behavior but intentions are the variables that have the highest influence value on variabellean behavior Strong intentions will support success in the implementation of lean behavior in the implementation of hospital lean management. dr. Iskak has a strong intention in supporting the implementation of lean behavior, through the strong efforts of the organization members in realizing lean behavior in hospital lean management. In order to prepare intentions, it is necessary to have the readiness of each individual. Microsoft Office Translator